DISSEMINATION BY GREEK TEAM: THOUSANDS REACHED - Irene Kamberidou; Karteroliotis, Konstantinos; Venetsanou, Fotini (Creating a tech tool to promote European Traditional Sports and Games from an intergenerational and inclusive perspective, ERASMUS PLUS Small Collaborative Partnership-GEO-LUDENS, 2018)
Dissemination report - Over 3, 450 reached to date that can be counted, in addition to those we have not counted or estimated, such as the uploads in over 10 websites, social media, networks, databases and homepages accessed, reached or visited by thousands, e.g. https://en.uoa.gr, as well as faculty emails and discussion folders/conversation pages (DEP and SOC), open access e-classes and project partners Facebook shares, to name a few. This report also includes a sample photo of our students linking into GeoLudens (See: Creating a tech tool to promote European Traditional Sports and Games from an intergenerational and inclusive perspective, ERASMUS PLUS Small Collaborative Partnership-GEO-LUDENS) © Kamberidou, I; Karteroliotis, K.; Venetsanou, F. (8/6/2018). Dissemination by Greek Team - Thousands Reached. School of Physical Education and Sport Science, National and Kapodistrian University of Athens (NKUA). Dissemination report following GEO-LUDENS (579689-EPP-1-2016-1-ES-SPO-SSCP) five working sessions in Athens, Greece, May 30/31-June 1, 2018.